Microbial Diversity and Non-volatile Metabolites Profile of Low-Temperature Sausage Stored at Room Temperature - Han, Hongjiao; Li, Mohan; Peng, Yanqi; Zhang, Zhenghan; Yue, Xiqing; Zheng, Yan (Frontiers in Microbiology, 2021)
Sausage is a highly perishable food with unique spoilage characteristics primarily because of its specific production technology. Changes in microbial composition and metabolites are critical factors in determining the quality of sausage during storage. This study developed a low-temperature sausage model without any preservatives and coated it with natural casing. We characterized the microbiota and non-volatile metabolites in the sausage stored at 20℃ for up to 12 d. Bacillus-velezensis was the most prevalent species observed after four days. Lipids and lipid-like molecules, organoheterocyclic compounds, organic acids and their derivatives were the primary non-volatile metabolites. The key non-volatile molecules were mainly involved in bioamine metabolism, protein catabolism and beta-oxidation. These findings provide useful information for the optimization of sausage storage conditions.